Preoperative Plasmapheresis for Elective Thymectomy in Myasthenia Patient: Is It Necessary?. (11th June 2013) - Saeteng, Somcharoen; Tantraworasin, Apichat; Siwachat, Sophon; Lertprasertsuke, Nirush; Euathrongchit, Juntima; Wannasopha, Yuttaphan
Abstract : Background . Role of plasmapheresis before thymectomy remains controversial. The aim of this study is to determine the peri-operative and post-operative outcome of a thymectomy between performing and not performing a pre-operative plasmaphreresis. Patients and Methods. A retrospective chart review study was conducted in Chiang Mai University Hospital between January 2006 and December 2011. There were 86 myasthenia patients divided into two groups; Preoperative plasmapheresis group (PPG) and no preoperative plasmapheresis group (NPPG). The primary outcome involved post-operative extubation and the secondary outcome included post-operative complications, 28 day mortality and length of hospital stay. Results. Eighty-six patients were enrolled in this study. The number of patients who had a history of myasthenic crisis at any time or within one month in the PPG was significantly more than those in the NPPG. Muscle power and forced expiratory vital capacity in the NPPG was higher than that in the PPG. The postoperative extubation rate was similar in both groups. After controlling for the propensity score, there were no statistically significant differences in both of primary and secondary outcomes. Conclusion . The results of this study shows no significant differences between both groups in all outcomes, therefore the pre-operative plasmaphresis is not necessary for elective thymectomy.